Moderating Risks, Bolstering Growth - World Bank (Washington, DC, 2013)
Half a year ago, Russia's economic prospects looked uncertain. The global economy was losing momentum, the expansion in the euro area was grinding to a halt and commodity prices were beginning to fall. Yet, while output growth is slowing this year in line with weaker growth in Europe and elsewhere, Russia's latest economy performance has been solid, though aided by favorable oil prices. The economy returned to the pre-crisis peak towards the end of last year, supported by strong consumption, as growth held steady at the same rate as in 2010. In 2011, measured in current dollars, Russia's economy was the ninth biggest in the world, compared to the eleventh biggest in 2007. This year, Russia's output might exceed US$2 trillion. Equalizing for prices difference with purchasing power parity, Russia's economy is already the sixth biggest today. The current account looks strong thanks to a large surplus in the trade balance, and the Central Bank of Russia added again in 2011 to its stock of foreign reserves. Employment returned to pre-crisis levels even earlier than output, and wages grew at a solid pace. Inflation reached its lowest level in two decades. Inequality declined and consumption levels of low-income households improved. The fiscal balance returned to a surplus. And while average public debt levels in advanced economies exceeded 100 percent of growth domestic product (GDP) in 2011, Russia's public debt was no more than 10 percent of GDP. Economic policies can help to shore up Russia's resilience in a volatile economic environment, diversify its economy, and strengthen its growth potential. First, fiscal policy should be used to rebuild fiscal buffers while oil prices are high. This will not only help to prepare for the next crisis, but also make sure that fiscal policy does not become procyclical as the output gap closes. Furthermore, monetary policy should continue to focus on low inflation, and financial policies on strengthening oversight. Finally, removing structural barriers to growth can help to bolster investment and productivity. Improving the business environment will go a long way to make the most of the economic benefits of Russia's World Trade Organization accession in summer 2012.